2006
DOI: 10.1136/ard.2006.053488
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome is common among middle-to-older aged Mediterranean patients with rheumatoid arthritis and correlates with disease activity: a retrospective, cross-sectional, controlled, study

Abstract: A high, albeit comparable to the control population, prevalence of MetS was found in middle-to-older aged patients with rheumatoid arthritis. The correlation of rheumatoid arthritis disease activity with MetS suggests that the increased prevalence of coronary heart disease in patients with rheumatoid arthritis may, at least in part, be attributed to the inflammatory burden of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
115
10
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(155 citation statements)
references
References 32 publications
19
115
10
11
Order By: Relevance
“…In India, also higher prevalence of MS has been reported from Silchar (39.28% in RA and 20 % in controls) and Chandigarh (31.57%in RA and 14.9%). 19,[21][22][23][24][25][26][27] When exploring the clinical and biochemical parameters in present study, RA patients had lower HDL, higher systolic BP and higher diastolic BP compared with healthy controls, a difference that was statistically significant. These results are in accordance with observations made by Rostom et al and Pandey et al 16,26 We did not find any significant correlation of body mass index (BMI), waist circumference and sugar between two groups.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In India, also higher prevalence of MS has been reported from Silchar (39.28% in RA and 20 % in controls) and Chandigarh (31.57%in RA and 14.9%). 19,[21][22][23][24][25][26][27] When exploring the clinical and biochemical parameters in present study, RA patients had lower HDL, higher systolic BP and higher diastolic BP compared with healthy controls, a difference that was statistically significant. These results are in accordance with observations made by Rostom et al and Pandey et al 16,26 We did not find any significant correlation of body mass index (BMI), waist circumference and sugar between two groups.…”
Section: Discussionmentioning
confidence: 92%
“…[15][16][17][18][19] The reason may be the different criteria used to define MS in different studies, however the results have still varied in different studies using the same criteria, which can be explained by the diversity of the study population characteristics, disease presentation and treatment regimen.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[60][61][62] That syndrome represents an association of conditions having in common insulin resistance and increased abdominal fat, which are closely related to infl ammation. 63 That relation to infl ammation can justify the higher prevalence of MS in patients with RA, 9,64-67 and the higher disease activity found in patients with RA who also have MS. [66][67][68] Dessein et al 69 have shown a 14%-19% prevalence of MS among patients with RA, and two other studies have not shown a greater prevalence of MS among patients with RA. 68,70 The presence of MS in the population without RA has been associated with a greater chance of cardiovascular events and higher overall mortality.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…63 That relation to infl ammation can justify the higher prevalence of MS in patients with RA, 9,64-67 and the higher disease activity found in patients with RA who also have MS. [66][67][68] Dessein et al 69 have shown a 14%-19% prevalence of MS among patients with RA, and two other studies have not shown a greater prevalence of MS among patients with RA. 68,70 The presence of MS in the population without RA has been associated with a greater chance of cardiovascular events and higher overall mortality. 71 There were no studies assessing the higher prevalence of myocardial infarction or stroke associated with MS in the population with RA, 72 but the presence of coronary artery calcifi cation, which can be diagnosed in a test and increases the likelihood of a cardiovascular event, has been associated with MS in that population.…”
Section: Metabolic Syndromementioning
confidence: 99%